Analisa Daya Saing dan Faktor-Faktor yang Mempengaruhi Ekspor Kerajinan Rotan Tahun 1993-2012 - Prasetio, Sugeng; Swara, I Wayan Yogi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 6, Juni 2015 (pp. 608 - 745), 2015)
Indonesia is the world's largest producer of rattan. This study aims to investigate the influence of the United States dollar exchange rate, gross domestic product of forest products and production quantities of the Indonesian rattan handicraft export volume and competitiveness of other countries. In addition, this research aims to determine the competitiveness of Indonesian Rattan and China using RCA index (Revealed Comparative Advantage). This study uses secondary data from the years 1993-2012 using Eviews 3 analysis program. The results of data analysis showed simultaneous US Dollar exchange rate, Gross Domestic Product and Total Production Forest Products significantly to the volume of exports of Indonesian Rattan craft in period 1993-2012. In partial test US Dollar exchange rate, and the amount of production has a significant positive effect on the volume of exports of Indonesian Rattan in period 1993-2012. Gross Domestic Product variable results negatively affect export volumes Rattan Indonesia period 1993-2012. Individually, the competitiveness of the export volume of rattan Indonesia and China has a fairly high competitiveness for RCA index ? 1, but the competitiveness of Indonesia is still weak when compared with China. Indonesia still needs to improve its competitiveness in order to increase the contribution to national revenue.
Keywords: Export rattan, US Dollar exchange rate, Gross Domestic Product of Forest Products, Total Production, Competitiveness